Hearing loss in a post COVID-19 patient - Chakraborty, Sayan; Maharatna, Sayan; Reddy, Chandra Shekar; Gupta, Gaurav; Baitha, Upendra; Jorwal, Pankaj; Biswas, Ashutosh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
With the advent of COVID-19 pandemic, there has been a myriad of long-term complications in post-COVID patients. In these patients, one of the rare but dreaded symptoms reported is sudden onset sensorineural hearing loss (SNHL) that has been reported mostly during active infection. We followed up with these patients in our outpatient department and came across one patient of SNHL. We conducted a literature search in PubMed and Google Scholar but couldn’t come across any such care report from India. We are hereby reporting the first case of SNHL in a post-hospitalised COVID-19 from India presenting after 3 months of hospital discharge, with no history prior otologic illness, intake of ototoxic drugs or any head injury. Post-COVID patients can present with weird symptoms including hearing loss apart from other commonly reported post COVID 19 sequelae.